Validation of the Pediatric Early Warning Score to determine patient deterioration from illness - Lenny Elita; Silvia Triratna; Erial Bahar (Indonesian Pediatric Society, 2016)
Background Patients who enter the emergency room (ERER) present with a variety of conditions, ranging from mild to critical. As such, it may be hard to determine which patients are in need of intensive care unit treatment. The Pediatric Early Warning Score (PEWS) has been used to identify signs of critical illness in pediatric patients.Objective To validate the PEWS system for assessing signs of critical illness in pediatric patients at Dr. Mohammad Hoesin Hospital, Palembang.Methods Subjects were children aged 1 month to 18 years who received treatment in the ERER and Pediatrics Ward inDr. Mohammad Hoesin Hospital in March to April 2015. Assessment with PEWS was based on vital sign examinations. Scores ranged from 0 to 9. The PEWS was generally taken twice, first in the ER , then after 6 hours in the ward. We obtained the cut-off point, sensitivity, and specificity of PEWS, in terms of need for pediatric intensive care unit (PICU) treatment.Results One hundred fifty patients were included in this study. Patients with PEW score of 5 or greater in the ER were relatively more likely to be transferred to the PICU, with a sensitivity of 94.4% and a specificity of 82.5%. The cut-off point obtained from the ROC curve was score 4.5 with AUC 96.7% (95%CI 93.4 to 99.9%; P<0.001).Conclusion A PEWS score of cut-off â‰¥5 may be used to determine which patients are in critically ill condition requiring treatment in PICU.